Homogenization of a nonlinear drift-diffusion system for multiple charged species in a porous medium - Bhattacharya, Apratim; Gahn, Markus; Neuss-Radu, Maria (Nonlinear analysis. Real world applications, 2022)
We consider a nonlinear drift-diffusion system for multiple charged species in a porous medium in 2D and 3D with periodic microstructure. The system consists of a transport equation for the concentration of the species and Poisson’s equation for the electric potential. The diffusion terms depend nonlinearly on the concentrations. We consider non-homogeneous Neumann boundary condition for the electric potential. The aim is the rigorous derivation of an effective (homogenized) model in the limit when the scale parameter ε tends to zero. This is based on uniform a priori estimates for the solutions of the microscopic model. The crucial result is the uniform L∞-estimate for the concentration in space and time. This result exploits the fact that the system admits a nonnegative energy functional which decreases in time along the solutions of the system. By using weak and strong (two-scale) convergence properties of the microscopic solutions, effective models are derived in the limit ε→0 for different scalings of the microscopic model.